Bax and Bcl‐2 are involved in the apoptosis induced by local testicular heating in the boar testis. (23rd February 2017) - Xi, H; Fan, X; Zhang, Z; Liang, Y; Li, Q; He, J
Contents: The aim of this study was to determine whether the effect of Bax and Bcl‐2 on the apoptosis of germ cells is caused by local testicular heating (42°C, 1 hr) in boar testis. The testes of three boars were exposed to 42°C for 1 hr. Three other boars were assigned as control (no heat treatment). After 6 hr of heat treatment, all boars were castrated and the testes were harvested. Immunohistochemical results showed that a redistribution of Bax was caused by heat stress, and Bcl‐2 was expressed in the cytoplasm and nucleus. Western blot analyses and quantitative real‐time polymerase chain reaction (QRT‐PCR) showed that the protein and mRNA levels of Bax and Bcl‐2 were increased after local testicular heating. The number of TUNEL‐positive cells was increased in the seminiferous tubules compared with the control after local testicular heating. These results suggested that local testicular heating induced the apoptosis of germ cells by regulating the Bax and Bcl‐2 protein levels.